Root and aerial growth of corn subjected to different biological managements in seed treatment with Bacillus aryabhattai - Mendes, Diego França; Cabral Filho, Fernando Rodrigues; Andrade, Christiano Lima Lobo de; Ventura, Matheus Vinícius Abadia (Brazilian Journal of Science, 2025)
Plant growth-promoting rhizobacteria (PGPR) can be an option to mitigate the impact of abiotic constraints in different cropping systems in the tropical semi-arid region. Therefore, the objective of this study was to evaluate the biometric growth parameters and root system of corn plants subjected to the use of Bacillus aryabhattai via seed treatment and furrow application. The trial was conducted in a commercial area in the southwestern region of Goiás, Brazil. The experiment was set up in a randomized block design with four treatments (T1 – Control; T2 – B. aryabhattai (4 mL kg-1 of seed) via seed treatment; T3 – B. aryabhattai (200 mL ha-1) via furrow application; T4 – B. aryabhattai (300 mL ha-1) via furrow application) and five replications, totaling 20 experimental plots. Root parameters (maximum root length (cm); root dry mass (g); root volume (cm3)) and biometric parameters (plant height (cm); ear insertion height (cm); stem diameter (mm); prolificacy (number of ears per plant); number of leaves) were evaluated. The application of Bacillus aryabhattai led to increases in root system volume and stem diameter in corn plants.